2014
DOI: 10.1186/2052-9538-1-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of carbon monoxide is ineffective as a long-term therapy to reduce obesity in mice fed a high fat diet

Abstract: BackgroundPrevious studies have demonstrated that induction of heme oxygenase-1 results in weight loss in several rodent models of obesity. However, the specific role of the heme oxygenase-1 metabolite, carbon monoxide (CO), in this response has yet to be established. We recently reported that chronic treatment with CO releasing molecules results in prevention of weight gain in mice fed a high fat diet. In the present study, we sought to determine the effect of chronic CO inhalation on the development and reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
(31 reference statements)
1
5
2
Order By: Relevance
“…Interestingly, the present results show no effect of approximately six weeks of daily CO inhalation (1 hour/day for 40 days) on body weight or insulin action in mice with established obesity. It is difficult to reconcile the differences between our findings and that of Hosick et al [8,9]. Since some of the beneficial effects of CO are mediated by an increase in reactive oxygen species [25], this response may be abrogated in mice with established weight stable obesity because of the already high levels of ROS [26].…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…Interestingly, the present results show no effect of approximately six weeks of daily CO inhalation (1 hour/day for 40 days) on body weight or insulin action in mice with established obesity. It is difficult to reconcile the differences between our findings and that of Hosick et al [8,9]. Since some of the beneficial effects of CO are mediated by an increase in reactive oxygen species [25], this response may be abrogated in mice with established weight stable obesity because of the already high levels of ROS [26].…”
Section: Discussioncontrasting
confidence: 55%
“…Hosick et al demonstrated that carbon monoxide releasing molecules promote weight loss and improve insulin action [8]. Although 10 weeks of CO inhalation appears to reduce body weight, this effect is transient and completely absence at 35 weeks [9]. Interestingly, the present results show no effect of approximately six weeks of daily CO inhalation (1 hour/day for 40 days) on body weight or insulin action in mice with established obesity.…”
Section: Discussioncontrasting
confidence: 44%
See 3 more Smart Citations